Analisis Kadar Kalsium (Ca) pada Air Minum Isi Ulang yang Diperjualbelikan di jalan Abdul Kadir Kota Makassar - Nismawati Nisma; Rifkawati S Lalundo (Jurnal Media Laboran, 2020)
Refill drink water is one the people alternative for fulfill clean water. But the quality refill drink water contaminated industry waste and processing less good in addition well water many contents chalk of calcium, magnesium, and iron. This experiment mean to analysis the content refill drink water sold on the street Abdul Kadir city of Makassar, this experiment type laboratorik observational quantitative use complexsometri method titration step. The sample technique of this research is use the total sampling method taken from 5 water depots at Abdul Kadir city of Makassar. The results of laboratory test on 5 sample of refill drink water taken from 5 drink water depots at Abdul Kadir city of Makassar have calcium content of each sample A = 16,83 mg/l, sample B = 22,84 mg/l, sample C = 14,02 mg/l, sample D =22,84 mg/l, and sample E = 20,04 these result not exceed 75 mg/l qulity standards of calcium therefore the water of health for consumption